Characterization of a New Aluminium Alloy for the Production of Wheels by Hybrid Aluminium Forging. (2015) - Tocci, M.; Pola, A.; La Vecchia, G.M.; Modigell, M.
Abstract: Recently, an innovative technique called Hybrid Aluminium Forging (HAF) has been developed as a combination of casting and forging processes. In the present paper the characterization of a new Al-Si-Mg alloy with Cr addition is reported; it was used in a preliminary study to evaluate its suitability for the production of wheels by HAF process. At first, calorimetric analysis was performed to identify solid fraction change with temperature for process optimization. The alloy after heat treatment shows good strength and hardness, but poor ductility, while Cr modifies the morphology of Fe-containing intermetallics. Finally, rheological measurements show a shear thinning behaviour of metal in semi-solid condition.